The Effect of Virtual Lab (VL) Game-Based Guided Inquiry Learning on Students’ Science Literacy in Indonesia - Faresta, Rangga Alif; Safana, Mega; Suhardi, Rizal M. (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Indonesian students consider studying science as a challenging subject. They regarded science as a difficult subject to be perceived. Consequently, Indonesian students showed a low result in science performance. The inquiry learning method incorporated in the virtual lab has been used to tackle this issue. However, there is a crucial debate that both teacher and students are not familiar with this integration. Therefore, the aims of this systematic review is to investigate the effect of  virtual lab based on Inquiry learning on students’ science literacy. This systematic literature method was used to provide evidence from many literatures related to virtual lab and science literacy. This provided an overview of current knowledge of  virtual lab effectiveness on student’s science literacy and insight into the methodological developments in this field of research. The result indicates that virtual lab can improve students’ science literacy. There are three factors to support this findings. First, virtual Lab provides students on learning with a deeper understanding of scientific concepts and critical thinking. Second, virtual Lab provides more interactive and engaging learning experience for students. Third, virtual Lab enhanced collaboration among students, teachers and researchers that improved the learning experience